2020
DOI: 10.1038/s41467-020-16206-8
|View full text |Cite
|
Sign up to set email alerts
|

A self-operating broadband spectrometer on a droplet

Abstract: Small-scale Fourier transform spectrometers are rapidly revolutionizing infrared spectro-chemical analysis, enabling on-site and remote sensing applications that were hardly imaginable just few years ago. While most devices reported to date rely on advanced photonic integration technologies, here we demonstrate a miniaturization strategy which harnesses unforced mechanisms, such as the evaporation of a liquid droplet on a partially reflective substrate. Based on this principle, we describe a self-operating opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Aside from difficulties in integration with planar light sources, a drawback of these devices is that the spectral resolution is limited by the maximum optical path length difference (OPD) allowed by the actuator travel range (60), which in turn is constrained by, for instance, the pull-in effect (whereby, below a threshold separation, the mirrors will uncontrollably and rapidly attract together) (2,6). Very recently, it has been demonstrated that the evaporation of a droplet atop the end of an optical fiber can also function as a system analogous to a scanning FT spectrometer, to obtain the absorption spectra of liquid analytes (61).…”
Section: Fourier Transform Microspectrometersmentioning
confidence: 99%
“…Aside from difficulties in integration with planar light sources, a drawback of these devices is that the spectral resolution is limited by the maximum optical path length difference (OPD) allowed by the actuator travel range (60), which in turn is constrained by, for instance, the pull-in effect (whereby, below a threshold separation, the mirrors will uncontrollably and rapidly attract together) (2,6). Very recently, it has been demonstrated that the evaporation of a droplet atop the end of an optical fiber can also function as a system analogous to a scanning FT spectrometer, to obtain the absorption spectra of liquid analytes (61).…”
Section: Fourier Transform Microspectrometersmentioning
confidence: 99%
“…As noted above, a feature of the analysis of the optical properties of condensed media is the need to obtain spectra with the least distortion, since it is necessary to solve ill-posed inverse problems. Due to the small size of the C12880MA and C11708MA spectrometers, their spectral resolution r(λ) is limited and is about 9 nm and 14 nm, respectively [22,23]. Although in many practical problems of analyzing the properties of condensed media this resolution may be sufficient, the problem of analyzing the possibilities of improving the equivalent spectral resolution of the considered microspectrometers obtained by using digital processing of the recorded spectra remain urgent [24].…”
Section: Improvement Of Equivalent Spectral Resolution Using Wiener F...mentioning
confidence: 99%
“…Moreover, in order not to distort the shape of the instrumental function, it is necessary to use a measurement circuit that is equivalent to the circuit for recording spectra S(λ) of diffusely scattered radiation. The numerical aperture NA of the considered spectrometers is equal to 0.22 [22,23], and the corresponding angle α = 2•arcsin(NA) ≈ 26 • . Radiation fluxes in the solid angle Ω shown in Figure 2 participate in the formation of the spectrum S(λ).…”
Section: Equipment For Spectra Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Miniaturized spectrometers show ultracompact footprint, portability, and integrability and thus possess great potential in the applications of in situ analysis systems, on-chip spectroscopy characterizations, hyperspectral imaging, etc . Significant efforts have been devoted to realize miniaturization of spectrometers, such as miniaturized dispersive optics, narrow-band filter systems, Fourier transform microspectrometers, and computational spectrum reconstruction. Among these approaches, spectrum reconstruction using filter-free photodetectors based on semiconductor materials with different band gaps is one of the most promising methods for spectral analysis. For instance, Yang et al reported a microspectrometer with a graded-band-gap CdS x Se 1– x nanowire, whose footprint was reduced to around 100 μm .…”
Section: Introductionmentioning
confidence: 99%